Inhibitory control mediates the interaction between serotonin transporter gene (5-HTTLPR) and peer victimization on adolescent depressive symptoms - Lin, Xiaonan (Sci Rep, 2021)
Many efforts have been devoted to investigating the effect of the interaction between the serotonin transporter gene (5-HTTLPR) and environment (G × E) on depression, but they yield mixed results. The inconsistency has suggested that G × E effects may be more complex than originally conceptualized, and further study is warranted. This study explored the association among 5-HTTLPR, peer victimization and depressive symptoms and the underlying mediating role of inhibitory control in this association. A total of 871 Chinese Han adolescents (M(age) = 15.32 years, 50.3% girls) participated and provided saliva samples from which the 5-HTTLPR was genotyped. This study found that 5-HTTLPR interacted with peer victimization in predicting depressive symptoms. Adolescents carrying L allele reported more depressive symptoms than SS carriers when exposed to higher level of peer victimization. Furthermore, adolescents’ inhibitory control deficits mediated the association between 5-HTTLPR × peer victimization and depressive symptoms. These findings suggested that one pathway in which G × E may confer vulnerability to depressive symptoms is through disruptions to adolescents’ inhibitory control system.